2016
DOI: 10.1002/lt.24611
|View full text |Cite
|
Sign up to set email alerts
|

Left lobe living donor liver transplantation in adults: What is the safety limit?

Abstract: Small-for-size syndrome (SFSS) is the most significant cause of graft loss after living donor liver transplantation (LDLT), especially after left lobe (LL) LDLT in adults. The safety limit of applying LL-LDLT in adults without severe SFSS with a high rate of lethality needs to be determined. A total of 207 LL-LDLTs in adults since September 2005 were evaluated to analyze the risk factors for severe SFSS, defined as a serum total bilirubin concentration of ≥20.0 mg/dL after LDLT. Although there were no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 33 publications
1
65
1
Order By: Relevance
“…The current study found that SFS RL graft and SFS LL graft did not have much difference when patient survival is concerned - which echoes the results in the literature[38,39] - but the SFS RL grafts had better survival than the SFS LL grafts ( P = 0.049). This study is a single-center retrospective study.…”
Section: Discussionsupporting
confidence: 87%
“…The current study found that SFS RL graft and SFS LL graft did not have much difference when patient survival is concerned - which echoes the results in the literature[38,39] - but the SFS RL grafts had better survival than the SFS LL grafts ( P = 0.049). This study is a single-center retrospective study.…”
Section: Discussionsupporting
confidence: 87%
“…Because it was ensured that the postperfusion PP was <18 mm Hg in all low-GRWR grafts, it is not surprising that the PP was not found to be a significant factor in their outcome. Others have also found MELD, (45,46) age, (47) and PP (5) to be important in this situation. Unlike in some other studies, (14,38) PF was not an important determinant of outcome of low-GRWR grafts in our study.…”
Section: Discussionmentioning
confidence: 89%
“…A major feature of ERAT is the longer CIT compared with ordinary LT (17). In addition, ERAT procedures are more complex than LT and hepatectomy so a longer operative time and more intraoperative blood loss seem inevitable (10).These are two poor prognostic indicators for LT recipients and hepatectomy patients because they may lead to graft loss due to the high incidence of postoperative biliary and arterial complications or severe hepatic dysfunction (18). Based on the above theory, the liver function, quality and estimated RLV of ELRA patients need to meet higher requirements.…”
Section: Discussionmentioning
confidence: 99%